MICROCIRCULATION REMODELLING IN CHILDREN WITH ARTERIAL HYPERTENSION. (June 2018) - Rogowska, A.; Obrycki, L.; Niemirska, A.; Litwin, M.
Abstract : Objective: Microvascular changes with rarefication of small arterioles and neuronal damage are regarded as a late complication of arterial hypertension. New optical technologies allow to analyze retinal vessels density and thickness of neuronal layer of retina. The aim of our study was to analyse retinal thickness and vascular density and its relationship with central systolic blood pressure (cSBP), central pulse pressure (cPP), subclinical target organ damage (TOD) in a non-selected group of children with primary (PH) and secondary hypertension (SH). Design and method: 72 children (22 girls) in mean age 15.5 ± 2.5 years with PH (39) and SH (33) were included to the study. Retinal vessel density and retinal thickness was measured with optical coherent tomography. cSBP and cPP was estimated from pulse wave analysis assessed by oscillometric method. Subclinical TOD was assessed as carotid artery intima-media thickness (cIMT), pulse wave velocity (PWV) and left ventricular mass (LVM). Results: Patients with PH and SH did not differ in terms of foveal and parafoveal thickness, superficial and deep vascular density of foveal and parafoveal areas of retina. When patients were divided according to presence or not of hypertensive subclinical TOD it was found that patients with increased cIMT had lower foveal thickness, foveal superficial and deep vessels density and greater foveal avascular zone (all p < 0.05). Foveal and parafoveal thickness correlated negatively with cPP and augmentation index (p < 0.05). Left ventricular hypertrophy (LVH) and increase of PWV was not associated with changes in foveal thickness and retinal vascular density. Conclusions: Arterial hypertension in children and adolescents is associated with early remodelling and rarefication of microcirculation expressed as lower foveal and parafoveal thickness, increase of avascular foveal area and decreased density of both superficial and deep foveal vessels. These changes were especially expressed in those of hypertensive children in whom subclinical arterial injury was also present and were associated with elevated central blood pressure.